1999
DOI: 10.1034/j.1398-9995.1999.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde: an occupational hazard in the hospital setting

Abstract: Our report indicates the importance of glutaraldehyde as an occupational hazard among exposed health-care workers. Intervention in the workplace, training of personnel handling this chemical, and accurate health surveillance may reduce the risk of developing occupational asthma due to glutaraldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 11 publications
0
53
0
1
Order By: Relevance
“…Formaldehyde is used in the hospital setting for cold sterilization of endoscopes and other medical instruments inadequate to put into autoclave. The Mean levels of formaldehyde in American hospitals vary from 0.1-0.8 ppm 1,2) . OSHA reported that one-third out of 1.3 million American workers exposed to formaldehyde are working in medical and paramedical institutions and organizations 3,4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formaldehyde is used in the hospital setting for cold sterilization of endoscopes and other medical instruments inadequate to put into autoclave. The Mean levels of formaldehyde in American hospitals vary from 0.1-0.8 ppm 1,2) . OSHA reported that one-third out of 1.3 million American workers exposed to formaldehyde are working in medical and paramedical institutions and organizations 3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde is widely used in manufacturing of insulating foams, resins and wood industries. Formaldehyde is also a byproduct of engine exhaust, photochemical smog and incinerator and cigarette smoke 1,2) . One of the most important uses of formaldehyde is for its disinfectant properties and pathology laboratory for tissue fixation in hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, continued vigilance is needed for the control and monitoring of workplace environments where GA is used and also for the ongoing assessment of health effects among exposed workers. (35,52) • Replace GA with alternative disinfectant such as hydrogen peroxide, peracetic acid-hydrogen peroxide (PAHP) or orthophthaldehyde (53, 54) Minimization • Skin contact and vapor inhalation should be minimized by using personal protective devices such as masks and gloves (33,36,52) • Reduce the number of people working in areas where GA is being used (35) • Spills of GA-containing liquids should be immediately cleaned up as soon as they occur (35,52) • Extraction fans should be installed, and preferably, push/pull ventilation systems (27,33,35,36,53) • All devices that contain GA solutions should be covered and sealed when not in use and only opened for the duration of use (33, 35, 36, 52) • Training and education for staff with emphasis on appropriate occupational hygiene techniques as mentioned above (33,35,52) …”
Section: Discussionmentioning
confidence: 99%
“…Hemminki and others (22,23) conducted two retrospective studies of the relationship between spontaneous abortions and GA exposure among health care workers, and found no correlations. The irritant properties of GA are well known in humans however (26)(27)(28), and probably share many similarities with animal models. A reasonably linear relationship between exposure dose and irritation has been experimentally demonstrated in animals (18), and this assumption is probably appropriate for humans.…”
Section: Toxicity To Humansmentioning
confidence: 99%
See 1 more Smart Citation